“Efecto de productos biológicos y fungicos para el control de alternaria y marssonina, en el cultivo de brócoli (brassica oleracea) híbrido royal favor F-1 HyB, enn la provincia de Lamas” - Silva Correa, Indira Cecilia (2014)
The present investigation entitled "Effect of biological products and fungal control A/ternaria and Marssonina in growing broccoli (Brassica oleracea) hybrid Royal Favor F 1 Hyb in the province of Lamas ", aimed to assess the effect of biological and fungal products to determine which has a greater effect doses for the control of Alternaria and Marssonina and perform economíc analysis for each treatment. Statistical design of randomized complete block (RCBD} was used with three blocks and five treatments for a total of 15 experimental units. The results indicate that, by applying phytosanitary control treatments T4 (2 l.ha-1 of Kasugamycin + 0,2 kg.ha·1 of Benomyl) and T3 (2,5 1.ha·1 comptex beneficia! microorganisms) showed greater effect control and resistance to A/ternaria and Marssonina, being so, the incidence of A/ternaria and Marssonina was only 10% for both treatments and severity of A/ternaria per attack was 3,3% for T3 and T4 3%, and 2,6% Marssonina for both treatments. The phytosanitary control by applying the T1 (0,2 l.ha-1 Trichoderma harzíanum) and T2 treatments (0,5 kg.ha·1 bacteria! consortium + 0,250 l.ha·1 Trichoderma harzianum), were found to be lower effect on control and resistance to attack by A/ternaria and Marssonina . He obtained the followíng results, for the incidence of Alternaría was 20 % for T1 and 13% for T2 and Marssonina was 10 % for T1 and 13% for T2, and in severity from attack A/ternaria was 6 % for T1 and 5.7% for T2 and Marssonina attack was 3,3 % and 3,6 % for T1 toT2. The T4 processes (2 f.ha-1 of Kasugamycin + 0,2 kg.ha-1 of Benomyl) and T3 (2,5 l.ha-1 complex of beneficia! microorganisms) with averages of 11 934,37 kg.ha-1 and 10 966.67 kg.ha-1 yield; 381,9 grams and 350,9 grams of the inflorescence and finally 14,7 cm and 15,7 cm in diameter of the inflorescence respectively were the best average, and these statistically equal. T3 (2,5 l.ha-1 complex beneficia! microorganisms), T4 (2 l.ha·1 of Kasugamycin + 0.2 kg.ha-1 of Benomyl) and T2 (0,5 kg.ha-1 bacteria1 consortium + 0,250 l.ha-1 Trichoderma harzianum) with averages of 29,4 cm, 29,0 cm and 28,5 cm in plant height, leaf 18,2, 17,9 and 18,1 sheets teaves per plant respectively were found to be statistically equal, surpassing their averages far treatments T1 (0,2 l.ha-1 Trichoderma harzianum) and TO (control). The T3 (2,5 l.ha-1 complex of beneficia! microorganisms) with respect to stem diameter, was the treatment showed the highest average with 4,2 cm statistically outperforming all other treatments. The T3 (2,5 l.ha-1 complex of beneficia! microorganisms ) and T4 treatments (2 l.ha-1 of Kasugamycin + 0,2 kg.ha-1 of Benomyl) showed higher rates to 1, with values of 8/C equal to 1,08 and 1,26 respectively and positive returns of 8,40% and 25,74 % respectively, which meant that net income exceeded net outflows. Key words : Effects , biologícal , fungat, Kasugamycin , Benomyt , attack, treatment , dose, farming, broccoli, profitability, production, performance, cost.